Estudo fitoquímico e avaliação da capacidade leishmanicida e cicatrizante cutânea das espécies Arrabidaea chica Verlot. (pariri) e Vernonia brasiliana Less. (assa-peixe) - SÁ, Joicy Cortez de (2015)
Leishmaniasis comprises a complex of diseases that affect humans and other mammals, ranging from a mild cutaneous type to a severe visceral form. The standard therapy using pentavalent antimonials is concerning due to its side effects. The search for alternative, effective and less toxic treatments has driven to the development of studies using natural products. Thus, this study aimed to evaluate the potential cytotoxic, leishmanicidal and healing effects of Arrabidaea chica and Vernonia brasiliana. For this were prepared the crude ethanolic extracts and chloroform, methanol and ethyl acetate fractions of A. chica and V. brasiliana, followed by phytochemical analysis and gas chromatography and mass spectrometry. Additionally, it was also extracted the essential oil of V. brasiliana. After phytochemical analysis, the following evaluations were made: in vitro cytotoxic assay, with the determination of cytotoxic concentration via MTT colorimetric assay; in vitro antileishmanial screening and determination of the inhibitory capacity of 50% of L. amazonensis promastigotes and amastigotes forms after 24, 48 and 72 h under the effect of crude ethanolic extracts, oil and fractions of A. chica and V. brasiliana; and wound healing activity in surgical lesions of Swiss Webster mice treated topically with 10 mg/g of the crude ethanolic extract of A. chica for 21 days, with further histological analysis. Phytochemical screening showed that the plants under study have flavonoids, tannins, anthocyanins, esters, triterpenes and chalcones. The leishmanicidal potential of the crude extract and fractions of A. chica showed satisfactory results in concentrations from 60 to 155.9 µg/ml, depending on the type of fraction. The ethanol extract, oil and fractions of the leaves of V. brasiliana have a markedly in vitro leishmanicidal activity than A. chica, with an IC50 15 times lower. In electron microscopy significant damage was observed in cell membranes, cytoplasm and flagellar pocket of the parasite after treatment with V. brasiliana. The cytotoxicity assay showed that both plants are not cytotoxic in leishmanicidal concentrations, with a selective ratio higher to the parasite than to the host cell. Topical preparation with the crude extract of A. chica presented in the initial phase, angiogenesis, collagen deposition and epithelialization more pronounced than the control group, but that did not persist throughout the 21 days of observation. These results demonstrate that compounds extracted from A. chica and V. brasiliana are potential leishmanicidal agents, which stimulates further studies in order to improve its action on the parasite, identifying bioactive substances for the development of new drugs.